Surgical Management of Pilocytic Astrocytoma of the Optic Nerve: A Case Report and Review of the Literature - Ifeoluwa Apanisile; Tamás Karosi (Case Reports in Oncological Medicine)
Optic nerve astrocytomas (ONAs) are frequent types of optic nerve gliomas (ONGs), which can affect the visual pathway. An 18-year-old male patient was admitted to our department with right-sided intraorbital/retrobulbar swelling, which progressively grew over several months. Clinical examination showed right-sided diplopia, mydriasis, low visual acuity (0.4), exophthalmus (3 cm), epiphora, and severe retrobulbar pain. There was a family history of high-grade (IV) astrocytomas in which two of the family members died due to the disease. Preoperative MRI scan revealed a soft tissue mass around the retrobulbar area of the right eye with intact orbital bony walls. Surgery was performed whereby it was dissected freely from the muscles and was separated from the optic nerve and the globe. Histopathologic analysis confirmed a benign astrocytoma. The follow-up examination revealed no recurrent or residual tumor. A systemic review of the literature indicates that early diagnosis and experienced multidisciplinary management are required in case of unilateral, resectable forms of ONAs with no distant metastasis, in order to provide a long-time survival of patients. Surgical intervention of unilateral ONAs is a relatively safe procedure, allowing complete or partial tumor removal with minimal morbidity and low recurrence rate.